(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Smartphones allow end users to perform several tasks while being on the move. As a consequence, end users require their personal smartphones to be connected to their work IT infrastructure. In the smartphone domain, the Android OS is by far the most popular platform with major market share. More and more companies nowadays provide mobile versions of their desktop applications. As a consequence, end users require their personal smartphones to be connected to their work IT infrastructure. In the smartphone domain, the Android OS is by far the most popular platform with major market share. More and more companies nowadays provide mobile versions of their desktop applications. Company confidential data should be stored in a separated space of the mobile storage. Due to Improper maintenance of location and activity manager the data there are data sharing, data leakage and data loss between different user profiles. In proposed work each profile details can be stored externally. The External Storage makes the directory for the each profile which can be used to store the information of the profiles which outperforms all the issues in all Existing technologies